The Impact of Type D Personality Traits on the Career Readiness of College Students With and Without Disabilities. (January 2017) - Reid Yates, Jenna A.; Wong, Alex W. K.; Strauser, David R.; Heft Sears, Susann J.
The primary purpose of the study was to investigate the relationship of Type D personality and perceived career readiness in a group of college students with and without disabilities. The findings of the study revealed no significant differences in levels of career readiness and Type D personality across disability groups. Results also revealed that Type D traits did have a significant relationship with career readiness variables, and that this relationship is particularly significant for college students with disabilities. Results also indicated that for individuals with disabilities, both Type D traits (negative affect and social inhibition) have an effect on different dimensions of career readiness. Implications of the results are discussed within the context of rehabilitation counselors and professionals. Future directions for research are also offered.